2018
DOI: 10.1111/pace.13442
|View full text |Cite
|
Sign up to set email alerts
|

Prospective survey of implantable defibrillator shock anxiety in Japanese patients: Results from the DEF‐Chiba study

Abstract: Female sex, secondary prevention, and experience of ICD shock therapy are important risk factors affecting shock anxiety in Japanese patients. Attention should be paid to the after-effects of ICD shock in these patients, regardless of the shock type, with particular attention to women and patients who require secondary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Individual and group differences in FSAS scores may reveal subgroups with psychological treatment needs. For instance, female patients consistently report higher levels of FSAS shock anxiety than men . Interestingly, female patients in a Japanese sample reported higher levels of shock anxiety but also exhibited decreases in FSAS shock anxiety over time, whereas male patients exhibited increases in shock anxiety over time .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Individual and group differences in FSAS scores may reveal subgroups with psychological treatment needs. For instance, female patients consistently report higher levels of FSAS shock anxiety than men . Interestingly, female patients in a Japanese sample reported higher levels of shock anxiety but also exhibited decreases in FSAS shock anxiety over time, whereas male patients exhibited increases in shock anxiety over time .…”
Section: Resultsmentioning
confidence: 92%
“…For instance, female patients consistently report higher levels of FSAS shock anxiety than men . Interestingly, female patients in a Japanese sample reported higher levels of shock anxiety but also exhibited decreases in FSAS shock anxiety over time, whereas male patients exhibited increases in shock anxiety over time . Spouses, mainly women, endorsed higher levels of shock anxiety on FSAS than ICD patients, highlighting the fear of disruption even for spouses .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Researchers have also studied the effect of device acceptance, perceived support from healthcare professionals, race (African Americans scoring higher on FSAS), and number of shocks experienced (appropriate or inappropriate). Moreover, secondary prevention was a consistent risk factor across multiple studies . The success of the FSAS even prompted the validation of a German version by Ritzka et al, which again showed the importance of both consequence and trigger stimuli .…”
mentioning
confidence: 97%